CLIPS: Enriching interorganizational R&D project management by a project culture focus - Dieterich, Katharina; Ohlhausen, Peter (International Journal of Information Systems and Project Management, 2023)
Project managers still face management problems in interorganizational Research and Development (R&D) projects due to their limited authority. Addressing a project culture which is conducive to cooperation and innovation in interorganizational R&D project management demands commitment of individual project members and thus balances this limited authority. However, the relational collaboration level at which project culture manifests itself is not addressed by current project management approaches, or it is addressed only at a late stage. Consequently, project culture develops within a predefined framework of project organization and organized contents and thus is not actively targeted. Therefore, a focus shift towards project culture becomes necessary. This can be done by a project-culture-aware management. The method CLIPS actively supports interorganizational project members in this kind of management. It should be integrable in the common project management approaches, that with its application all collaboration levels are addressed in interorganizational R&D project management. The goal of this paper is to demonstrate the integrability of the method CLIPS and show how it can be integrated in common project management approaches. This enriches interorganizational R&D project management by a project culture focus.